Upaya Penurunan Kehilangan Air Menggunakan Metode Water Balance (Teknik Step Test - Sounding) Dan Analisis Finansial (Studi Kasus: Graha Indah, Pdam Tirta Manggar Kota Balikpapan) - Sekar Inggar Rengganis (ITB Journal Publisher, LPPM ITB, 2022)
The most common problems that occur in the distribution of drinking water are mainly caused by the high rate of water loss or Non-Revenue Water (NRW). According to the results of research in both DMA Graha Indah namely DMA Graha Indah 1 and DMA Graha Indah 2 have a fairly high rate of water loss that is for DMA Graha Indah 1 46.94% (78% physical loss; 22% non-physical loss) which is equivalent to 163,012 m3/ year and DMA Graha Indah 2 is 59.2% (87% physical loss; 13% non-physical loss) or 211,017 m3/ year. This research outlines using the Method Water Balance (WB) which includes techniques step test, sounding, and efforts to repair pipe leaks while for non-physical losses with water meter accuracy techniques. The results obtained after the repair of the leak is a decrease in the physical loss by 4% for DMA Graha Indah 1 and 41.16% DMA Graha Indah 2. This study also made a piping network simulation using the WaterCAD software V8i so that it can be ascertained that pipelines are leaking in the area by looking at the pressure drop along the pipe section. In striving to reduce water loss in the Graha Indah Area, 3 scenarios are made, for all scenarios remaining 5% are non-physical losses, while for physical scenarios there are remaining 10%, 7,5%, and 5%, respectively, and then all financial scenarios are analyzed financially. with an analysis period of 5 years. The chosen scenario based on the financial feasibility with an analysis period as long as 5 years (i=4.98%). The results of financial feasibility proves that scenario 3 is a selected scenario for DMA Graha Indah 1 which NPV, BCR, and BEP values ​​respectively Rp. 9,430,810,135; 3.3295; 0.1086 and for DMA Graha Indah 2 the chosen scenario is scenario 3 which NPV, BCR, and BEP values respectively Rp 8,417,476,299; 2.767; 0.146.